2013
DOI: 10.1002/adsc.201201107
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I)‐Catalyzed Coupling Cyclization of Methyl Perfluoroalk‐2‐ynoates with 2‐Aminobenzonitriles: Synthesis of 2‐Perfluoroalkylated Quinolines

Abstract: An efficient route to 2-perfluoroalkylated quinoline derivatives through the copper(I)-mediated coupling-cyclization of 2-aminobenzonitriles with methyl perfluoroalk-2-ynoates is described. Moderate to excellent yields have been achieved under mild conditions. The reaction mechanism is also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…[13] X-ray crystallography of 3b revealed the ester group attached to the quinoline 3-position and the R F group attached to the quinoline 2-position. Based on the above observations and the previous literature, [11j,11l] together with our recent work on the synthesis of 2-perfluoroalkylquinolines, [12] a plausible mechanism is shown in Scheme 2. The formation of the sole product 3 could be explained by the highly regioselective coordination of the base-activated amino group in 1 with the more electrophilic carbon atom of the triple bond in 2.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…[13] X-ray crystallography of 3b revealed the ester group attached to the quinoline 3-position and the R F group attached to the quinoline 2-position. Based on the above observations and the previous literature, [11j,11l] together with our recent work on the synthesis of 2-perfluoroalkylquinolines, [12] a plausible mechanism is shown in Scheme 2. The formation of the sole product 3 could be explained by the highly regioselective coordination of the base-activated amino group in 1 with the more electrophilic carbon atom of the triple bond in 2.…”
Section: Resultssupporting
confidence: 58%
“…Such findings can be easily explained by the increased nucleophilicity of the -NH 2 group due to the presence of a p-EDG (-OMe), thus affecting the efficiency of the first Michael addition step in this two-step heterocyclization by improving the reaction yields. [12] The investigation of the electronic nature of substituent R 2 also showed that substrates with an electron-rich group such as p-OMe in the aryl group of the alkyne moiety gave better yields (Table 2, Entry 11 vs. 13).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…[29] The reaction commences with a Michael addition of the amino group of compound 41 to alkynoate 1 to generate 43, which undergoes successive deprotonation by piperidine, Analogously, through the treatment of o-aminophenyl ketones 48 and methyl perfluoroalk-2-ynoates 1 in the presence of a catalytic amount of Cu 2 O, a series of 2-perfluoroalkylated quinolines 49 were obtained with excellent regioselectivity (Scheme 17). [30] Most o-aminophenyl ketones, whether with electron-withdrawing or electron-donating groups, were suitable for this protocol.…”
Section: Synthesis Of Quinoline Derivativesmentioning
confidence: 99%
“…A facile CuBr‐catalyzed one‐pot procedure was developed by us to synthesize 2‐perfluoroalkylquinolines from 2‐aminobenzonitriles 41 and methyl perfluoroalk‐2‐ynoates 1 (Scheme ) 29…”
Section: Application Of Methyl Perfluoroalk‐2‐ynoates In the Synthesimentioning
confidence: 99%